2013
DOI: 10.1016/j.ajic.2013.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic and other effects and compliance with long-term respirator use among medical intensive care unit nurses

Abstract: Long-term use of respiratory protection did not result in any clinically relevant physiologic burden for health care personnel, although many subjective symptoms were reported. N95 compliance was fairly high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
302
2
16

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(335 citation statements)
references
References 12 publications
15
302
2
16
Order By: Relevance
“…These findings, and recent evidence of physiological tolerance to long-term (12 hours) use of an N95 FFR by nonpregnant women, 27 suggest that N95 FFRs are likely to be safe for use by healthy, pregnant women and should serve as a stimulus for a larger study. Research reporting that the use of medical/surgical masks results in similar physiological effects as N95 FFR 37 implies that these protective facemasks are also safe for use during pregnancy.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…These findings, and recent evidence of physiological tolerance to long-term (12 hours) use of an N95 FFR by nonpregnant women, 27 suggest that N95 FFRs are likely to be safe for use by healthy, pregnant women and should serve as a stimulus for a larger study. Research reporting that the use of medical/surgical masks results in similar physiological effects as N95 FFR 37 implies that these protective facemasks are also safe for use during pregnancy.…”
Section: Discussionmentioning
confidence: 72%
“…At low work levels over 1 hour, mixed inhalation/exhalation N95 FFR deadspace CO 2 (2.8%-2.9%) 23,24 exceeds ambient levels and results in rebreathing of CO 2 ; however, CO 2 retention is generally minimal, because respirator deadspace CO 2 ≤2% is fully compensable in the short term. 26 These findings, along with the mild increase (ie, 7.6 mm Hg) in PtcCO 2 reported with 12 hours of N95 FFR use by female health care workers, 27 suggest that CO 2 retention sufficient to cause fetal distress (PtcCO 2 ≥60 mm Hg) 28,29 should not occur in healthy pregnant women wearing an N95 FFR. The finding of a significant effect of N95 FFR use on PtcCO 2 over time during exercise ( P = .04) is related to the rebreathing of higher CO 2 levels generated during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…However, prior research [7] has demonstrated no significant effect in core temperatures during up to 2 h of wearing N95 FFRs at low-moderate work rates, and investigation a included single day testing in which subjects wore N95 FFRs for a total of 4 h with only 30 min breaks between successive hours of exercise and no clinically significant changes in TMT were noted. Though recent data has indicated that elevated BMI and age may have a relationship with thermal discomfort experienced with wearing N95 FFRs [24], we did not analyze the possible impact of BMI or age on TMT because few of our subjects were overweight (9 %) or age ≥30 years (12 %). Only adult subjects were enrolled, so that we cannot comment on the impact of protective facemask wear on children.…”
Section: Discussionmentioning
confidence: 99%
“…The main test variable in this study is the survival of bacteria that were loaded on N95 FFRs that were decontaminated by various methods under worst‐case temperature and humidity, which prevail when an FFR is placed in a zipper bag in a healthcare worker's pocket with the goal of preventing cross‐contamination, and touching of the respirator . In the experiment, B. subtilis spores were the tested microbial strain; a six‐jet Collison nebulizer (BGI, Waltham, MA) sprayed the spores into a test system, shown in Figure , where they were loaded on N95 FFRs by suction to simulate the respiratory flow of workers during intensive activity .…”
Section: Methodsmentioning
confidence: 99%